2018
DOI: 10.1097/rct.0000000000000748
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Virtual Monoenergetic Images on Pulmonary Vasculature Using the Dual-Layer Detector-Based Spectral Computed Tomography

Abstract: Suboptimal enhanced pulmonary arterial CT studies can be salvaged using low-energy VMI generated from the SDCT scanner. There were significant improvements of attenuation, SNR, and CNR at the optimal monoenergetic level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Based on prior studies, which reported an improvement in quantitative image quality by low-keV VMI+, [10][11][12][13][14][15][16][22][23][24] we aimed to assess if this beneficial effect could be exploited to improve endoleak detection. Increased iodine attenuation of low-keV VMI+ is based on the fact that their energy levels (40 and 50 keV) are closer to the k-edge of FIGURE 2.…”
Section: Discussionmentioning
confidence: 99%
“…Based on prior studies, which reported an improvement in quantitative image quality by low-keV VMI+, [10][11][12][13][14][15][16][22][23][24] we aimed to assess if this beneficial effect could be exploited to improve endoleak detection. Increased iodine attenuation of low-keV VMI+ is based on the fact that their energy levels (40 and 50 keV) are closer to the k-edge of FIGURE 2.…”
Section: Discussionmentioning
confidence: 99%
“…Schueller-Weidekamm et al compared standard 140 kVp CT angiography with the 100 kVp and demonstrated an increase in percentage of central and peripheral pulmonary arteries that could be evaluated with CT angiography (12). Recently, several investigators reported the added value of dual energy CT systems using VMI reconstructions in CT angiography studies (13)(14)(15)(16) (18). Ghandour et al, compared conventional (120 kVp) images with the optimal monoenergetic level and showed a significant improvement of attenuation, SNR and CNR using dual layer spectral CT, advocating the 50 keV images as the optimal monoenergetic level (14).…”
Section: Standard Cnr Clot Ratio Best Cnr Clot Ratiomentioning
confidence: 99%
“…In the current study, we found that the benefit of low kiloelectronvolt VMI is its potential to improve the suboptimal pulmonary CT angiography studies using rapid kVp switch dual energy CT. Several prior studies have assessed dual energy CT for suboptimal enhancement in the pulmonary artery, however the patient population and CT protocols of these studies were heterogeneous (14,19). Different contrast volumes and acquisition parameters were used.…”
Section: Standard Cnr Clot Ratio Best Cnr Clot Ratiomentioning
confidence: 99%
“…1). VMI at low energies (< 70 keV) are used to improve the signal from contrast, which can be used to salvage suboptimal vascular studies or prospectively use a lower dose of intravenous contrast [13]. High energy VMI can be used for decreasing artifacts, e. g. caused by metallic implants.…”
Section: Computed Tomographymentioning
confidence: 99%